The difference between socio-demographic factors with stigma and understanding towards mental health - Tan, Yi Jing; Dewi Nur Izzati Mohamed Noriman; Kok, Ann Gie; Peh, Serene Shee Sien; Nisrin Zaifulsham; Tharshana Rajasegaran; Yassika Davee Steven Cartdosa; Yvette Ethena Anak Gudom; Mohd Haazik Mohamed (Faculty of Psychology and Education, UMS, 2023)
Globally, university and college students show a rise in having serious mental illness. University students often perceive mental health topics as a stigma which result in refusing to seek help. The objective of this study is to determine the difference between socio-demographic factors with stigma and understanding towards mental health among students in Universiti Malaysia Sabah. There were 100 undergraduate students as our respondents were 100 undergraduate students aged between 18 and 25 years old from the University Malaysia Sabah. Snowball sampling and convenience sampling were used for data collection. Respondents were provided with a Google Form link to our questionnaire. T-test in current study revealed that there is no significant different between both groups of gender (male and female), relationship status (single and in relationship), income (B40 and M40) towards knowledge scores and attitudes score. Similarly, result of ANOVA test shows that no significant differences between age groups, ethnicity, religion, years of study towards knowledge and attitude score. 66% of the respondents revealed that they will talk to a friend or family member about their mental health problems. Although result shown there is no significant different of knowledge score and attitude score according to different demographics groups, however this study may add value to the data for Malaysia's study on mental health issues among psychology students.